Macrophytes communities associated to soil bioengineering techniques for erosion control in riverbanks - Santos, Maria Hosana; Holanda, Francisco Sandro Rodrigues; Lino, Janisson Bispo; Santos, Tássio Lucas Souza; Fontes, Cátia Santos; Moura, Marks Melo; Araújo Filho, Renisson Neponuceno (Iheringia, Série Botânica., 2020)
The objective of this study was to evaluate the temporal and spatial richness of aquatic macrophyte settlement in a right bank of the São Francisco river, northeastern Brazil. The botanical material was collected and assembled exsiccate from April 2014 to September 2015, totaling four samplings at the points identified as: Vegetated Slope (A); Vegetated Riprap (B); Eroded Slope (C), Cribwall (D); Vetiver Grass Contour Line (E). It was identified 66 species distributed in 23 families. The Vegetated Slope in the rainfall period presented higher species richness and diversity. The soil bioengineering techniques at points B, D and E presented a stable river bank, thus creating a favorable environment for a larger settlement of macrophytes.